Sasi (Gam): Local wisdom of Koiwai People in managing and utilizing the coastal and marine resources - sokoy, fredrik (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2022)
This article aims to describe and analyze in depth the practice of sasi (gam) in the culture of the Koiwai people in Kaimana Regency. They perceive sasi (gam) as an embodiment of local wisdom in the context of managing and utilizing coastal & marine resources, by highlighting the mechanism for enforcing sasi, sanctions and penalties, as well as analyzing the function and value of sasi for the Koiwai community and what changes have occurred. The method used is descriptive qualitative using an ethnographic approach. The location of the research is in Namatota Island, Kaimana Regency, West Papua Province. I used observation and interviews as data collection techniques. Also, data analysis includes the stages of data reduction, data presentation and data interpretation. The results of the research show that sasi (gam) in the Koiwai people is carried out at sea and on land which aims to maintain the level of resource availability which has implications for the balance of the ecosystem. In addition to conservation purposes, sasi (gam) also has functions and values ​​in social and economic aspects and maintains the order of the Koiwai community. However, on the other hand, there has been a shift caused by internal and external factors that threaten the sustainability of the practice of the sasi.